Innovative teaching of building technology to architecture students in the University of Malaya - Rao, S.P.; Hashim, H.; Arbi, E. (2008)
The built environment is an integral part of the infrastructure necessary for human survival. Current concerns over the environmental sustainability of our biosphere for future generations are being scrutinized on the fringes of higher education. The focus of this paper is on the teaching approaches of academicians of a public university in Malaysia, specifically on the integration of building technology and sustainability issues into the subjects offered. Architecture teaching involves not only the teaching of art and aesthetics but also the science of building. With the increased use of high-rise construction, intelligent building features as well as the use of the building services to make the buildings habitable, it becomes imperative that the students of architecture understand and appreciate the complexities of engineering systems to make the buildings sustainable and energy efficient, so that their carbon footprint is minimal. The process of architectural designs starts with the sketch design as well as a statement of design intent including sustainability and targets by the architectural student. At this point several major decisions were being made with respect to the orientation, fenestration, service cores, environmental control system etc. This paper presents a novel approach adopted in the Department of Architecture at the University of Malaya for the teaching of Building Analysis to year 3 students as well as Advanced Building Technology to Year 4 students in a five year Architectural programme.